2010
DOI: 10.1007/s11104-010-0573-1
|View full text |Cite
|
Sign up to set email alerts
|

Changing the soil surface management in vineyards: immediate and delayed effects on the growth and yield of grapevine

Abstract: In a changing context, farmers adapt their cropping systems and, in this respect, the response time of the soil-crop system (changes in the soil resources and in the grapevine vegetative or reproductive development) has to be considered to maintain its agronomic performances. This is particularly true for perennial crops such as grapevine. This paper aims to analyse the short- and long-term effects of changes in soil surface management on grapevine performances. Avineyard in which bare soil inter-rows had been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
35
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 27 publications
5
35
0
1
Order By: Relevance
“…Whereas, in other studies, it has been shown that cover-cropped vineyards do not always exhibit higher water stress compared to those with bare soil (Celette et al 2005;Ripoche et al 2011). Nevertheless, what it is commonly shown is that cover crop clearly interacts with the vines by improving soil properties, including spatial and temporal modifications of the water within the soil profile (Celette et al 2008).…”
Section: Cover Cropsmentioning
confidence: 90%
“…Whereas, in other studies, it has been shown that cover-cropped vineyards do not always exhibit higher water stress compared to those with bare soil (Celette et al 2005;Ripoche et al 2011). Nevertheless, what it is commonly shown is that cover crop clearly interacts with the vines by improving soil properties, including spatial and temporal modifications of the water within the soil profile (Celette et al 2008).…”
Section: Cover Cropsmentioning
confidence: 90%
“…Spatial structure refers to service crop location in the field: full surface, only rows or inter-rows, one inter-row out of two or more (Figure 3). Such a choice impacts competition between service crops and grapevines, and thus berry production, particularly in non-irrigated conditions (Ripoche et al, 2011a). Sowing one inter-row out of two might act as partial root-zone drying (PRD) technique, without altering grapevine yield and improving berry quality (Poni et al, 2007;Lopes et al, 2011).…”
Section: Service Crop Strategy Designmentioning
confidence: 99%
“…In all these cases, permanent cover crops growing in the interrows, when they were eliminated during the summer months to avoid severe competition with the vines, tended to have a weakening effect on both vegetative and reproductive growth, despite the presence of deep soils and/or fertilization. However, a recent study demonstrated that response times in grapevine vigor to changes in floor management varied annually (Ripoche et al 2011a). In the first year after incorporation of a permanent cover crop (intercrop destroyed), the yield was still greater in a bare soil treatment or where cover crop was established in previously bare alleys (intercrop introduced).…”
Section: Cover Cropsmentioning
confidence: 99%